Detection of somaclonal variation in aquatic plant pearl grass (Hemianthus micranthemoides) - Nor Hasima, Mahmod; Tajul Afif, Abdullah; Nur Izyan, Sukimin (2019)
Hemianthus micranthemoides is an ornamental plan used for foreground plant in aquarium decorations. In Malaysia, the plant available on market is regenerated through tissue culture techniques which expose the risk for somaclonal variation. The objectives of this study are to identify suitable Random Amplified Polymorphic DNA (RAPD) markers for determining somaclonal variation rate in micropropagated plantlets of H. micranthemoides and to observe the effects of somaclonal variation on the plantlet growth (area of spreadability, shoot and root length). Out of 20 RAPD primers screened by polymerase chain reaction (PCR) using mother plant, one was selected as a suitable marker to detect somaclonal variation of H. micranthemoides which was P15. Somaclonal variation rate of the H. micranthemoides was determined by analyzing the RAPD-PCR bands. The results showed somaclonal variation was observed at the fifth subculture (S5) with the percentage of polymorphic bands of 50 % when compared to mother plant. Repeated subclutures has affected the growth of the regenerates negatively. It was shown that as the number of subculture increased, the growth of plantlet decreased in terms of decreasing shoot and root length as well as area of spreadability. This findings serves as a guide especially for tissue culturist to minimize subculture numbers when micropropagating H. micranthemoides.